The Influence of Storytelling Strategies, Customer Engagement, and Visual Content on Food Agritourism Sustainability: A Study of Wondis Chocolate, Kulon Progo - Dara Salsabila Rianti; Hermawan; Anjar Dwi Astono (Proceedings of the International Conference on Entrepreneurship (IConEnt), 2025)
Sustainable tourism has become a strategic approach addressing complex ecological, social, and economic challenges in the post-pandemic era. Food agritourism is recognized as a strategic vehicle for creating sustainable value creation aligned with Sustainable Development Goals (SDGs). This study aims to analyze the influence of storytelling strategies, customer engagement, and visual content on food agritourism sustainability at Wondis Chocolate, Kulon Progo. The research employed a quantitative approach with explanatory design involving 100 tourist respondents selected through purposive sampling. Data were collected using Likert scale questionnaires and analyzed through multiple linear regression. Results indicate that storytelling strategies, customer engagement, and visual content have positive and significant effects on food agritourism sustainability, both partially and simultaneously. Visual content demonstrates the strongest influence, followed by customer engagement and storytelling. This research contributes theoretically to destination marketing theory development and provides practical recommendations for optimizing sustainable agritourism marketing strategies.